What is Ecdyonurus sumatranus Ulmer, 1939? A contribution to the knowledge of the genus Rhithrogena in the Oriental Region (Ephemeroptera, Heptageniidae) - Sartori, Michel (Zootaxa, 2014)
The species Ecdyonurus sumatranus Ulmer, 1939 was described from Sumatra based on a female imago and a single nymph. It was designated as the type-species of the genus Ecdyonuroides Dang, 1967, erected because of the peculiar morphology of the nymph. This genus was put into synonymy later and the species is currently known as Thalerosphyrus sumatranus (Ulmer, 1939). The female imago holotype of Ecdyonurus sumatranus Ulmer, 1939 is reinvestigated and revealed to belong to the genus Rhithrogena Eaton, 1881. The combination Rhithrogena sumatrana (Ulmer, 1939) comb. nov. is thus proposed. The nymphs described by Ulmer (1939) from Java sub. nom. Rhithrogena parva (?) are associated to this species, and are redescribed with new material coming from Java and Lombok. Rhithrogena parva (Ulmer, 1912) is redescribed based on the syntype series from Taiwan and male genitalia are illustrated for the first time. Supplementary description is provided for the nymph of Rh. parva and for the one of Rh. ampla Kang & Yang, 1994, also from Taiwan. The status of the subgenus Tumungula Zhou & Peters, 2004 is briefly discussed. The nymph associated by Ulmer (1939) to Ecdyonurus sumatranus is renamed Thalerosphyrus lamuriensis sp. nov. The genus Ecdyonuroides Dang, 1967 is considered as a synonym of Rhithrogena syn. nov.